The antiquity of Cyclocarya paliurus (Juglandaceae) provides new insights into the evolution of relict plants in subtropical China since the late Early Miocene. (19th October 2015) - Kou, Yixuan; Cheng, Shanmei; Tian, Shuang; Li, Bo; Fan, Dengmei; Chen, Yongjun; Soltis, Douglas E.; Soltis, Pamela S.; Zhang, Zhiyong
Abstract: Aim: The accumulation of supraspecific lineages in Asia has been linked to climatic changes and tectonic events starting in the Miocene, but few studies have extended the intraspecific history of relict plants in subtropical China back to the Early or Middle Miocene. In this study, we investigate the effects of events from the late Early Miocene onwards on the evolutionary history of a relict plant, Cyclocarya paliurus, in subtropical China. Location: Subtropical China. Methods: Sequence variation in two chloroplast intergenic spacers ( atp B –rbc L and psb A –trn H) and one nuclear gene ( PHYA ) was investigated across 57 populations of C. paliurus . Standard population genetic analyses, estimation of the most recent common ancestor of chloroplast haplotypes and diversification rate analyses were carried out, and Bayesian skyline plots were constructed. Results: The time to the most recent common ancestor of all 17 chloroplast haplotypes in C. paliurus was 16.69 Ma (95% HPD 8.42–27.86 Ma), which largely coincides with the initial intensification of the Asian monsoon and global climate cooling during the Early to Middle Miocene. Chloroplast lineage diversification started to increase in the early Late Miocene, with peaks at c . 9.6 Ma and c . 3.6 Ma, corresponding temporally to two subsequent intensification events of the Asian monsoon. Bayesian skyline plots of both markers revealed that C. paliurus could have experienced at least two waves of expansion since the middle Pleistocene. The distributions of chlorotypes and clades were both consistent with a multiple‐refugia model but with strong signals of range expansion. Main conclusions: This study provides a long evolutionary profile of an archaic plant species in subtropical China, dating from the late Early Miocene. Our results suggest that the occurrence of the Asian monsoon and associated tectonic events, as well as Pleistocene climate changes, had a pervasive influence on the phylogeographical structure of plants in subtropical China.